Tropical pediatrics: 2002 to 2015 - Santos Ocampo, Perla D; Santos Ocampo-Padilla, Cynthia (The Turkish Journal of Pediatrics, 2003)
It also presents the challenges that confront children in the tropics and their effects on the health of these children. These challenges include the technology divide, economic disparity, ecological changes, urbanization and industrialization, globalization, political instability, population explosion, and gender inequality. The paper paints a scenario of tropical pediatrics into the year 2015. Problems brought about by both underdevelopment and modernization, with urbanization and industrialization, will persist. Infectious diseases will continue to be the leading causes of deaths. The paper presents some significant achievements in the fight against tropical diseases and tries to predict what future progress will contribute to the alleviation of such diseases. The paper also outlines the commitment of the International Society of Tropical Pediatrics (ISTP) to improve the state of tropical pediatrics in the next 15 years.